Implementing the Problem-Based Learning Model to Enhance Critical Thinking Skills on the Theme of Environmental Diversity in Junior High School Students - Arfiany Nur Amalia; Fakhriyatus Shofa Alawiyah; Samira Agoro (Journal of Pedagogical and Teacher Professional Development, 2025)
This study aim to enhance critical thinking skills among Grade VII C students at State Junior High School Lumajang 2 during the 2023/2024 academic year through the implementation of the Problem-Based Learning (PBL) model. The subject was about environmental diversity, encompassing subtopics such as environmental comprehension, advocacy for preservation practices, sustainable development, and resource scarcity. The study was carried out in three cycles involving 32 students, with every cycle comprising two sessions. Data was gathered via questionnaires and processed with SPSS, assuring both validity and reliability. Descriptive statistics, frequency distribution, and validity and reliability tests were employed to analyze the data. The findings indicated advancements in students' critical thinking skills: Cycle I recorded scores of 68.75% in the first session and 81.25% in the second session. Cycle II recorded scores of 87,5% in the first session and 62.5% in the second session. Cycle III demonstrated improvements, with scores of 90.62% in the first session and 87.5% in the second session. The research determined that PBL effectively improved students' critical thinking skills.